2020
DOI: 10.21203/rs.3.rs-28271/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The current landscape of pre-exposure prophylaxis service delivery models for HIV prevention: a scoping review

Abstract: Background: Strengthening HIV prevention is imperative given the continued high HIV incidence worldwide. The introduction of oral PrEP as a new biomedical HIV prevention tool can be a potential game changer because of its high clinical efficacy and the feasibility of its provision to different key populations. Documenting the existing experience with PrEP service delivery in a variety of real-world settings will inform how its uptake and usage can be maximised. Methods: We conducted a scoping review using the … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…The unique situation of reduced physical contact and a societal lockdown may be a good opportunity to consider alternative forms of PrEP follow-up and sexual health services, such as online counselling or home-based sampling. 22 Additionally, we suggest further research is needed to investigate what minimum package for PrEP follow-up would be feasible and for whom.…”
Section: Discussionmentioning
confidence: 99%
“…The unique situation of reduced physical contact and a societal lockdown may be a good opportunity to consider alternative forms of PrEP follow-up and sexual health services, such as online counselling or home-based sampling. 22 Additionally, we suggest further research is needed to investigate what minimum package for PrEP follow-up would be feasible and for whom.…”
Section: Discussionmentioning
confidence: 99%
“…A recent review of delivery models for HIV prevention found only one dedicated study of PrEP delivery for trans women. 30 Our study provides evidence that PrEP uptake for trans communities could be enhanced by offering low threshold PrEP-only services outside primary care, messaging building on the facilitators we identified, and attending to structural barriers to PrEP. Furthermore, the barriers to PrEP uptake identified in the literature to date are only partially relevant-based on our evidence.…”
Section: % -mentioning
confidence: 74%
“…An ongoing national CDC learning collaborative includes 31 SHCs, 24 (77%) of which provide PrEP prescriptions to patients (CDC program data, personal communication). Although different models for PrEP implementation in SHCs have been described, 8,9 best practices for real-world integration of PrEP services into SHCs are ill defined. Ideally, PrEP should be readily accessible to patients, affordable, and implemented without disrupting other SHC services or placing unsustainable new demands on clinician time.…”
Section: Introduction/backgroundmentioning
confidence: 99%